Penggunaan Kartu Brizzi Terhadap Efektivitas Santri Dalam Meminimalkan Penggunaan Uang Tunai (Studi Kasus Pondok Pesantren Nurul Jadid Wilayah Al-Hasyimiyah) - alvan Fathony Fathony; Linda yas’a (JURNAL PROFIT, 2021)
This study aims to determine the mechanism and function of Brizzi cards and the effectiveness of santri in minimizing the use of cash. This study uses a qualitative type, the research instrument uses interview documentation and field observations. The results showed that: the use of Brizzi cards was very effective against the effectiveness of santri in minimizing the use of cash, especially in the Al-Hashimiyah region. Because with the use of Brizzi cards, the santri is given a limit on the use of balances in the transaction so that the santri can also manage the use of their money properly, the spread of cash decreases, and the case of frequent loss of money is rare, now also affecting the cooperative's cash income. Because students in the transaction have switched to using electronic money / Brizzi.